Gaga feminism sex, gender, and the end of normal - Halberstam, J. Jack 1961- (Boston, Massachusetts Beacon Press Books, 2012)
Analyzes the transformative political and societal shifts of recent decades that have paved the way for revolutionary conceptualizations of gender and marriage, using Lady Gaga as a symbol of a new era that embraces sexual fluidity.
Gaga feminism for beginners -- Gaga genders -- Gaga sexualities: the end of normal -- Gaga relations: the end of marriage -- Gaga manifesto.
Includes bibliographical references (pages 153-157)
Keywords: Lady Gaga; Feminism -- Social aspects; Sex -- Social aspects